2022
DOI: 10.1002/aoc.6807
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized plasmonic Pd–ZnO nanomaterials for visible light‐induced photobiogas production from industrial wastewater

Abstract: Plasmonic Pd–ZnO nano photocatalysts synthesized via a green chemistry approach represent an innovation of visible‐light‐induced photocatalysis that can be applied for photobiogas production from organic dye pollutants. Different plasmonic Pd–ZnO nanophotocatalysts have been synthesized via green microwave‐assisted methods using orange peel extract as a capping agent by adding different proportions (3, 5, and 7 wt%) from Pd‐metal plasmons. This fast and green innovative method anchored well distribution of Pd‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Nevertheless, the low surface area also decreases the charge transfer affecting the recombination, which diminishes the photocatalytic performance [ 13 ]. To overcome this issue, several studies have presented various kinds of strategies to increase the surface area and reduce the recombination of ZnO photocatalysts [ 14 , 15 , 16 ]. The application of ZnO doped with an alkaline earth metal, such as barium (Ba), was reported as the photocatalyst [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the low surface area also decreases the charge transfer affecting the recombination, which diminishes the photocatalytic performance [ 13 ]. To overcome this issue, several studies have presented various kinds of strategies to increase the surface area and reduce the recombination of ZnO photocatalysts [ 14 , 15 , 16 ]. The application of ZnO doped with an alkaline earth metal, such as barium (Ba), was reported as the photocatalyst [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…BaZnO exhibited a better photocatalytic performance than that of pure ZnO by around 1.4 times. The incorporation of Pd-metal plasmons into ZnO was presented as an effective way to improve the ZnO surface area [ 15 ]. The Pd-ZnO nanoparticles (NPs) were synthesized using a green microwave-assisted method from orange peel extract as a capping agent with a Pd addition.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent aggregation and reduce the size of the TiO 2 NP, it was indicated that the metallic Pd is evenly distributed throughout the TiO 2 matrix and on the surface. 23…”
Section: Resultsmentioning
confidence: 99%
“…2.4.2 Fuel-gas generation set-up. All prepared samples were subjected to the biogas generation efficiency test through employing a prototype as described by Mbrouk et al 23 The gas prototype A is a lab-scale UV reactor (ESI (S1) †), and the prototype concentrating solar reactor B is used under a nitrogen atmosphere for gas production. The photo-reactor A works with UV energy.…”
Section: Photocatalytic Degradation Set-upmentioning
confidence: 99%
See 1 more Smart Citation